Spatio-Temporal and Cultivar-Dependent Variations in the Cannabis Microbiome - Comeau, Dominique; Novinscak, Amy; Joly, David L.; Filion, Martin (Frontiers in microbiology, 2020)
The incipient legalization and commercialization of in Canada have promulgated research into characterizing the plant's microbiome as it promotes many facets of plant growth and health. The emblematic production of commercially important secondary metabolites, namely tetrahydrocannabinol (THC), cannabidiol (CBD) and terpenes, has warranted investigating the modulating capacity of these molecules on the plant microbiome. cultivars can be classified into chemotypes depending on the relative levels of THC and CBD they produce; their biosynthesis also varies spatially and temporally during the life cycle of the plant. To study the differential microbiome structure and diversity between cultivars in a spatio-temporal manner, we extracted microbial DNA from the rhizosphere, endorhizosphere, and phyllosphere during the entire life cycle of three different chemotypes; CBD Yummy (<1% THC/13% CBD), CBD shark (6% THC/10% CBD) and Hash (14% THC/ < 1% CBD). Illumina marker gene sequencing of bacterial (16S) and fungal (ITS) communities were coupled to the QIIME2, PICRUSt, and LEfSe pipelines for analysis. Our study describes spatio-temporal and cultivar-dependent variations in the fungal and bacterial microbiome of , and details strong cultivar-dependent variance in the belowground microbiome. Furthermore, the predicted pathway abundance of the bacterial microbiome is concomitantly subject to spatio-temporal variations; pathways related to lipid, amino acid, glucose and pentose metabolism were noteworthy. These results describe, for the first time, spatio-temporal and cultivar-dependent variations in the microbiome of produced under strict commercial settings. Describing the microbiome is the first step in discoveries that could help in engineering a plant growth and health promoting microbiome in future works.